2018
DOI: 10.2147/cmar.s181066
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting GIT1 reduces the growth, invasion, and angiogenesis of osteosarcoma

Abstract: BackgroundGIT1, a scaffold protein with ubiquitous multi-domain, is involved in many cellular processes. In recent years, it was proved that GIT1 participated in various tumors’ growth or metastasis. However, the biological function of GIT1 in osteosarcoma is still unclear. In this study, we aimed to investigate the role and mechanism of GIT1 in osteosarcoma.Materials and methodsHuman osteosarcoma tissues were obtained to investigate the distribution of GIT1. Adequate osteosarcoma cells were stably infected wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…HCC is the most common primary malignant liver tumor with abundant tumor vascular network, which provides the evidence for the clinical therapies targeted vascular endothelial growth factor (VEGF) for the treatment of unresectable HCC (2). Angiogenesis is critical to multiple tumor invasion and metastasis (3, 4). Targeted angiogenesis therapy is an important anti-tumor strategy at present and it is particularly important to understand the transcriptional regulation of tumor angiogenesis (5, 6).…”
Section: Introductionmentioning
confidence: 99%
“…HCC is the most common primary malignant liver tumor with abundant tumor vascular network, which provides the evidence for the clinical therapies targeted vascular endothelial growth factor (VEGF) for the treatment of unresectable HCC (2). Angiogenesis is critical to multiple tumor invasion and metastasis (3, 4). Targeted angiogenesis therapy is an important anti-tumor strategy at present and it is particularly important to understand the transcriptional regulation of tumor angiogenesis (5, 6).…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al discovered that MeCP2 facilitated cell growth by upregulating GIT1 expression in gastric cancer [ 20 ]. In osteosarcoma, GIT1 was discovered to be highly expressed, and GIT1 knockout repressed cell invasion, cell growth, and angiogenesis [ 21 ]. Consistent with our findings, GIT1 knockout was confirmed to inhibit tumor growth in breast cancer [ 11 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…OS cell-specific aptamer (LC09) -functionalized PEG-PEI-Cholesterol (PPC) lipopolymer encapsulating CRISPR/Cas9 plasmids encoding VEGFA gRNA and Cas9 in both orthotopic OS and lung metastasis, showed effective VEGFA genome editing in tumor, decreased VEGFA expression and secretion, inhibited orthotopic OS malignancy and lung metastasis [98]. Zhang et al evaluated G-protein-coupled Receptor Kinase Interactor-1(GIT1), as a target for the treatment of osteosarcoma and suggested that knowdown of GIT1 inhibited cell invasion and VEGF release in vitro and suppressed tumor growth, invasion, and angiogenesis in vivo, and also resulted in downregulation of hypoxia-inducible factor1α (HIF1α) and extracellular signal-regulated kinase (ERK1/2) pathways [99]. Moreover studies have shown that ALDH1B1, a subfamily of Aldehyde dehydrogenases (ALDHs), is upregulated in OS.…”
Section: Personalized Nanomedicine For Bone Disordersmentioning
confidence: 99%